Word meaning in Arabic from an Islamic perspective - Hj. Yaakub, Muhamadul Bakir (Hamdard Foundation Press, Pakistan, 2003)
Perhaps, it will strike some people as odd that a paper devoted to Islamization of Arabic is really needed since Islam and Arabic has always been sysnonymous. Indeed, it may even seem strange that there is a discussion about it at all. Nevertheless, the issue of meaning is extremely important. In fact, it has been debated and discussed since the time of Prohet Muhamad (peace be upon him)...